Uji Efek Analgetik Infusa Daun Jeruk Nipis (Citrus aurantifolia (Christm.) Swing) terhadap Mencit Putih (Mus musculus L) Jantan yang Diinduksi Asam Asetat 1% - Novia Sinata (Jurnal Penelitian Farmasi Indonesia, 2020)
Research has been carried out on the analgesic effect of infusion of lime leaves (Citrus aurantifolia (Christm.) Swing) on male white mice (Mus musculus L) induced 1% acetic acid.The purpose of this study was to see the effect of analgesic effect of infusion of lime leaves (Citrus aurantifolia (Christm.) Swing) on male white mice (Mus musculus L) using the Writhing Test method. Experimental animals were divided into 5 groups. The negative control group was only given aquades, a positive control group of acetyl salicylate acid with a dose of 1.3 mg / 20g BB which was suspended with 1% Na CMC, the treatment group was given a lime leaf infusion (Citrus aurantifolia (Christm.) Swing) with a concentration of 5 %, 10% and 20%.The experimental animals were given oral preparations as much as 1% BB, 30 minutes after which each group was induced with 1% acetic acid as much as 0.1 ml ip. The data obtained is processed using two-way Analysis of Variance (ANOVA). The results showed that the infusion of lime leaves at concentrations of 10% and 20% (Citrus aurantifolia (Christm.) Swing) has analgesic effects on mice induced 1% acetic acid, .significantly different from negative controls (p<0.05) but not as strong as acetyl salicylate (positive control) Keywords : Analgetic, infusion, lime leaves, acetic acid